Scaling readiness of biofortified root, tuber, and banana crops for Africa - Low, Jan; Ball, Anna-Marie; Ilona, Paul; Ekesa, Beatrice; Heck, Simon; Pfeiffer, Wolfgang H. (Springer, 2022)
This chapter describes the degree of readiness and use of biofortified root, tuber, and banana (RT&B) crops: sweetpotato, cassava, banana (cooking and dessert types), and potato. Efforts to develop and utilize orange-fleshed sweetpotato (OFSP), yellow cassava (VAC), and vitamin A banana/plantain (VAB) have been focused heavily in sub-Saharan Africa (SSA), where 48% of the children under 5 years of age are vitamin A-deficient. Iron-biofortified potato is still under development, and a recent study found high levels of bioavailability (28.4%) in a yellow-fleshed cultivar (Fig. 17.1). To date, adapted VAB varieties have been piloted in East Africa, and OFSP and VAC have scaled to 8.5 million households. The scaling readiness framework is applied to innovation packages underlying those scaling efforts to shed light on how scaling is progressing and identify remaining bottlenecks. Women dominate RT&B production in SSA, and women and young children are most at risk of micronutrient deficiencies; hence women’s access to technologies was prioritized. Lessons learned from these scaling efforts are discussed, with the goal of accelerating the scaling readiness process for other biofortified RTB crops. Implementing gender-responsive innovation packages has been critical for reaching key nutrition and income goals. Diverse partnerships with public and private sector players and investing in advocacy for an adequate enabling environment were critical for achieving use at scale. Future scaling will depend on more nutritious sustainable food systems being at the forefront, supported by continued improvement in breeding methodologies to adapt to climate change and enhance multiple nutrient targets more quickly and to increase investment in the input and marketing infrastructure that vegetatively propagated crops require.